Curcumenol Mitigates the Inflammation and Ameliorates the Catabolism Status of the Intervertebral Discs In Vivo and In Vitro via Inhibiting the TNFα/NFκB Pathway - Yang, Xiao; Li, Baixing; Tian, Haijun; Cheng, Xiaofei; Zhou, Tangjun; Zhao, Jie (Frontiers in Pharmacology, 2022)
Low back pain (LBP) caused by intervertebral disc degeneration (IVDD) is accredited to the release of inflammatory cytokines followed by biomechanical and structural deterioration. In our study, we used a plant-derived medicine, curcumenol, to treat IVDD. A cell viability test was carried out to evaluate the possibility of using curcumenol. RNA-seq was used to determine relative pathways involved with curcumenol addition. Using TNFα as a trigger of inflammation, the activation of the NF-κB signaling pathway and expression of the MMP family were determined by qPCR and western blotting. Nucleus pulposus (NP) cells and the rats’ primary NP cells were cultured. The catabolism status was evaluated by an ex vivo model. A lumbar instability mouse model was carried out to show the effects of curcumenol in vivo. In general, RNA-seq revealed that multiple signaling pathways changed with curcumenol addition, especially the TNFα/NF-κB pathway. So, the NP cells and primary NP cells were induced to suffer inflammation with the activated TNFα/NF-κB signaling pathway and increased expression of the MMP family, such as MMP3, MMP9, and MMP13, which would be mitigated by curcumenol. Owing to the protective effects of curcumenol, the height loss and osteophyte formation of the disc could be prevented in the lumbar instability mouse model in vivo.